Efektivitas Penggunaan Alat Peraga Edukatif (APE) Berbasis Limbah dan Alam Terhadap Pengembangan Motorik Halusdi Kelompok Bermain AZ-ZAHRA - Yuyun Yunengsih; Husni; Sofia Ratna Awaliyah Fitri (Hikamatzu | Journal of Multidisciplinary, 2025)
The limited availability of Educational Play Equipment (APE) in Early Childhood Education (PAUD) institutions hinders the optimization of child development. This study aims to determine the effectiveness of using waste-based and natural materials-based APE on the development of fine motor skills in early childhood in Kober AZ-ZAHRA, Cihideung Hamlet, Utama Village, Cijeungjing District, Ciamis Regency. The method used was descriptive quantitative with 10 children aged 4–5 years, teachers, and parents as subjects, which was carried out for five days. The intervention involved the creation and use of APE made by teachers and parents, including cardboard puzzles, bottle cap mazes, natural finger painting, clay playdough, and dried leaf collages. The results of the activity showed an average increase in children's fine motor skills by 40%, especially in eye-hand coordination, finger muscle strength, and creativity. Teachers and parents displayed high enthusiasm in the process of creating and implementing APE. In addition to being proven effective, this approach is economical and environmentally friendly and strengthens collaboration between schools and families in creating a creative and sustainable learning environment. The implications of the research emphasize the importance of teacher innovation and creativity in managing learning according to developmental targets, so that it can increase motivation and aspects of children's overall development..